2020
DOI: 10.35790/jbm.12.3.2020.31472
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Kasus Obstetri di Rumah Sakit Sebagai Pusat Rujukan Nasional

Abstract: This study aimed to evaluate obstetric cases referred to Prof. Dr. R. D. Kandou Central General Hospital Manado as a reference center in North Sulawesi. This study was a retrospective-descriptive study with all single delivery cases both vaginal and caesarean section delivery which had complete medical record data at January 1 – December 31, 2018 period in the Obstetrics Department of Prof. Dr. R. D. Kandou Hospital Manado. From the results of research, the number of single deliveries was 1357 cases of labor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A study by Lumentut (2020) showed Prof. Dr R.D. Kandou hospital is a national central general hospital with tertiary-level health facilities, thereby the normal delivery rate supposes to be low [40].…”
Section: Referrals and Region Of Originmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Lumentut (2020) showed Prof. Dr R.D. Kandou hospital is a national central general hospital with tertiary-level health facilities, thereby the normal delivery rate supposes to be low [40].…”
Section: Referrals and Region Of Originmentioning
confidence: 99%
“…A study by Lumentut (2020) showed Prof. Dr R.D. Kandou hospital is a national central general hospital with tertiary-level health facilities, thereby the normal delivery rate supposes to be low [40]. This is related to the existence of primary and secondary-level health facilities that can handle vaginal deliveries.…”
Section: Referrals and Region Of Originmentioning
confidence: 99%